The Influence of Spirituality on the Development of Financial Institutions at BMT Peta Jombang Branch - Laila Ma'Rufah; Naily El Muna (INCOME: Innovation of Economics and Management, 2024)
Islamic financial institutions are financial institutions that work according to the concept of sharia with the principle of profit lost sharing as the main method. This study aims to determine the influence of spirituality on BMT PETA Jombang Branch. This study tries to determine the extent of spiritual influence on BMT PETA Jombang Branch. This study aims to analyze the influence of the variables Spirituality (X) and Microfinance Institutions (Y). In this study, data were collected through a questionnaire method by distributing Likert-scale questionnaires to 70 respondents of BMT PETA Jombang Branch customers. Then an analysis of the data obtained was carried out using quantitative methods. The quantitative analysis used includes validity tests and reliability tests. The data analysis technique used is a simple linear regression test which functions to prove the research hypothesis. From the results of the analysis, it is known that the independent variables have a positive effect on the dependent variable.